Oxalate Diet Induced Chronic Kidney Disease in Dahl-Salt-Sensitive Rats Induces Uremic Cardiomyopathy - Dube, Prabhatchandra (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.